Contribution of two diagnosis tools to support interface situation during production launch - Surbier, L.; Alpan, G.; Blanco, E. (Cranfield University Press, 2009)
Firms are urged to constantly introduce new products. Hence, the New Product Development process should be mastered, especially its final phase, the production launch. This paper addresses the critical issue of the information exchange during production launch. Two diagnosis tools considering production launch as a key interface are presented. They permit to examine the information flows, to highlight their weaknesses and hence to find solutions for further improvements. This paper also presents the results of a case study where the diagnosis tools were implemented during a switchgear development project.
Organised by: Cranfield University
Keywords: New Product Development; Production Start-up; Information exchange; Intermediary objects